The role of the IFI and the EU Peace III Fund in creating sustainable peace in Northern Ireland and the border counties. Issue 8 (16th November 2016) - Khan, Saad; Byrne, Sean
ABSTRACT: NGOs aided by external economic aid can play a critical part in post-accord peacebuilding situations. This article explores the impact of the International Fund for Ireland and the European Union Peace III Fund in nurturing sustainable peace through development in Northern Ireland and the border counties of the Republic of Ireland by examining the perceptions and experiences of 107 local NGO leaders and 13 funding agency development officers. During the summer of 2010, 120 people were interviewed using semi-structured interviews in Derry city and nine border counties. The article explores the role of external economic international assistance aids in building sustainable development, reconciliation, and peace in Northern Ireland and the border counties.